Translation of Western Ideals in a Developing Country: A Critical Ethnography of Corporate Social Responsibility Practices in Bangladesh - Reza, Syed Muhammod Ali (Curtin University, 2017)
Relying on institutional theory, both from organizational and postcolonial perspectives, this study has investigated the local effects of the corporate social responsibility (CSR) practices of Western multinational companies (MNCs) in Bangladesh. The focus was on how local suppliers understand and cope with the demands from their multinational contractors to implement localised CSR policies. Using critical ethnography, this study has conducted a qualitative investigation with MNCs suppliers in the garment industry in Bangladesh.